2007
DOI: 10.1007/978-3-540-74796-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Assistive Technology: An Empirical Study

Abstract: Abstract. This paper analyzes the problem of evaluating elderly people's perception of assistive robots and domotic environments. Specifically, we focus on aspects related to the modalities in which interaction can occur between an elder user and an assistive robotic agent. Our work benefits from the products of project ROBOCARE, namely, a domestic environment in which sensors, intelligent software components and a domestic robot provide a set of cognitive support services for the elder user. This paper analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Prototype robots have been developed to support independent living, in order to help older adults who try to live in their homes for as long as possible, even when the user is functionally disabled. Several personal service robots have been developed, including Aibo (Fujita, 2001), Care-O-bot (Graf, Han, & Schraft 2004;Graf, Reiser, Hägele, Mauz, & Klein, 2012), Pearl (Pollack et al, 2002), iCat (van Breemen, Yan, & Meerbeek, 2005), Robocare (Cesta et al, 2007), Robot-Era robots (Cavallo et al, 2014), or Hobbit (Fischinger et al, 2016). In addition, the robots Huggable (Stiehl et al, 2006), Paro (Wada, Shibata, Musha, & Kimure, 2005), Companionable (Badii et al, 2009), Giraff (Coradeschi, Loutfi, Kristoffersson, Von Rump, Cesta, Cortellessa, 2011) and GiraffPlus (2014), amongst others, have been developed to provide emotional support and other companion functions.…”
Section: Introductionmentioning
confidence: 99%
“…Prototype robots have been developed to support independent living, in order to help older adults who try to live in their homes for as long as possible, even when the user is functionally disabled. Several personal service robots have been developed, including Aibo (Fujita, 2001), Care-O-bot (Graf, Han, & Schraft 2004;Graf, Reiser, Hägele, Mauz, & Klein, 2012), Pearl (Pollack et al, 2002), iCat (van Breemen, Yan, & Meerbeek, 2005), Robocare (Cesta et al, 2007), Robot-Era robots (Cavallo et al, 2014), or Hobbit (Fischinger et al, 2016). In addition, the robots Huggable (Stiehl et al, 2006), Paro (Wada, Shibata, Musha, & Kimure, 2005), Companionable (Badii et al, 2009), Giraff (Coradeschi, Loutfi, Kristoffersson, Von Rump, Cesta, Cortellessa, 2011) and GiraffPlus (2014), amongst others, have been developed to provide emotional support and other companion functions.…”
Section: Introductionmentioning
confidence: 99%
“…35 The functionalities of the robot connected the user with their family through verbal and visual interactions, sending a video stream in the case of dangerous situations, providing stimulation when the user performed physical exercises, and observing the user's behavior. 35 Cesta et al 64 reported a positive reaction from seniors regarding the use of a proactive robot in emergency situations. In contrast, Zsiga et al 35 found that seniors showed some concerns related to slow response of robots during a dangerous situation.…”
Section: Technological Issuesmentioning
confidence: 99%
“…We were able to use video material made for the Robocare project by the Institute for Cognitive Science and Technology of the Italian National Research Council for research by Cesta et al [29,30] (Figure 1). We made four video's of the robot representing the four conditions.…”
Section: Systemmentioning
confidence: 99%